2016
DOI: 10.1038/nrg.2016.13
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic modulators, modifiers and mediators in cancer aetiology and progression

Abstract: This year is the tenth anniversary of the publication in this journal of a model suggesting the existence of ‘tumour progenitor genes’. These genes are epigenetically disrupted at the earliest stages of malignancies, even before mutations, and thus cause altered differentiation throughout tumour evolution. The past decade of discovery in cancer epigenetics has revealed a number of similarities between cancer genes and stem cell reprogramming genes, widespread mutations in epigenetic regulators, and the part pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
577
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 717 publications
(600 citation statements)
references
References 270 publications
5
577
0
3
Order By: Relevance
“…Besides the large blocks of DNA hypomethylation (Hansen et al 2011;Berman et al 2012;Hon et al 2012;Timp et al 2014) and hypermethylation Coolen et al 2010;Forn et al 2013), other alterations as the activation of gene clusters (Bert et al 2013) and the increased somatic mutation rates observed in heterochromatic and late replicating regions (Schuster-Böckler and Lehner 2012;Polak et al 2015) point out that factors regulating high-order chromatin architecture (Dekker et al 2013;Gómez-Díaz and Corces 2014;Feinberg et al 2016) might play a principal role in the remodeling of the cancer genome (Rodriguez et al 2008a;Lizardi et al 2011;Kemp et al 2014;Lay et al 2015;Taberlay et al 2016). The contribution of Alu repeats to the setting and maintenance of chromatin domains and their regulation in normal and cancer cells is still unknown.…”
Section: Alu-related Determinants Of Global Genomic Hypomethylation Amentioning
confidence: 99%
“…Besides the large blocks of DNA hypomethylation (Hansen et al 2011;Berman et al 2012;Hon et al 2012;Timp et al 2014) and hypermethylation Coolen et al 2010;Forn et al 2013), other alterations as the activation of gene clusters (Bert et al 2013) and the increased somatic mutation rates observed in heterochromatic and late replicating regions (Schuster-Böckler and Lehner 2012;Polak et al 2015) point out that factors regulating high-order chromatin architecture (Dekker et al 2013;Gómez-Díaz and Corces 2014;Feinberg et al 2016) might play a principal role in the remodeling of the cancer genome (Rodriguez et al 2008a;Lizardi et al 2011;Kemp et al 2014;Lay et al 2015;Taberlay et al 2016). The contribution of Alu repeats to the setting and maintenance of chromatin domains and their regulation in normal and cancer cells is still unknown.…”
Section: Alu-related Determinants Of Global Genomic Hypomethylation Amentioning
confidence: 99%
“…Durch die Entwicklungen in der epigenetischen Forschung versteht man immer mehr über die biologischen Zusam- (Argentieri et al 2017;Feinberg et al 2016). Auch für die kardiovaskuläre Regulation (Sartori et al 2016), aber ebenso für kardiovaskuläre Risikofaktoren wie das metabolische Syndrom konnten systematische Veränderungen epigenetischer Markierungen nachgewiesen werden (Park et al 2017 (Spitzer et al 2016;Su et al 2015).…”
Section: "Familiäre" Belastung Als "Erworbener" Kardiovaskulärer Risiunclassified
“…Quantitative Figure 1: Methods of DNA methylation analysis by Lanlan Shena and Robert A. Waterlandb [26] 3 Mechanism Of Dna Demethylation DNA demethylation mechanism is found to be mediated by the ten-eleven translocation (Tet) enzymesTet1, Tet2, and Tet3 [14] . Tet In the first, iterative oxidation by Tet enzymes continues to oxidize 5hmC first to 5-formyl-cytosine and then to 5-carboxy-cytosine In the second,5hmC is deaminated by AID/APOBEC to form 5-hydroxymethyl-Uracil Consistent with the role of Tet in converting 5mC into 5hmC in vivo [13] , Proposed models of Tet-initiated DNA demethylation pathways.…”
Section: Dna Methylation Methods For the Specific Genelocus Specificmentioning
confidence: 99%